Optimisation of safety factor in the designing phase of a bracing study. (1st January 2011) - Telis, Eleftherios-Stamatios N.; Besseris, George J.; Stergiou, Constantinos
Quality tools assist engineering applications in fields never used before. The aim of this paper is to present a novel method for optimising the safety factor of a bracing project in the designing phase. In the presented methodology, the Taguchi analysis will be the quality method used. It produces the experimental runs by combining design variables that give the design characteristics (safety factor) measurements. The results of these experiments are calculated via finite elements analysis and the optimisation is also supported by ANOVA treatment. The blueprints used in this project are taken from a real-life case study. This method can be used as a useful guide tool for engineers in order to predict any design characteristic as long as the design variables which determine its value can de named and take discrete values (two/three or more each).